POLITICAL MATTER IN HISTORICAL GOVERNMENT OF TURKIYE’s ELECTION - Muhammet Ebuzer Ersoy (UNISSULA, 2023)
After two decades in power and more than a dozen elections, Turkey's authoritarian leader Recep Tayyip Erdogan knows how to work a room. At a taxi drivers' convention in Istanbul, they could not get enough of him. He controlled the crowd like the conductor of an orchestra. They cheered and clapped - and booed the opposition - on cue. The venue was a waterside convention centre in Istanbul, built during his time as mayor of the city. The rally reached a crescendo as the president delivered his parting shot: